2013
DOI: 10.2478/popore-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Studies on diversity of soil microfungi in the Hornsund area, Spitsbergen

Abstract: Abstract:We assessed culturable soil microfungal diversity in various habitats around Hornsund, Spitsbergen in the High Arctic, using potato dextrose agar (PDA) medium. Thermal growth classification of the fungi obtained was determined by incubating them in 4°C and 25°C, permitting separation of those with psychrophilic, psychrotolerant and mesophilic char− acteristics. In total, 68 fungal isolates were obtained from 12 soil samples, and grouped into 38 mycelial morphotypes. Intergenic spacer regions of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Among 78 fungal genera detected in the present study, 11 were previously reported from the Arctic soils, including Acremonium , Alternaria , Arrhenia , Arthrinium , Aspergillus , Cladosporium , Exophiala , Herpotrichia , Mortierella, Phialocephala, Oidiodendron , and Preussia 2 3 4 , and 3 were observed associated with the Arctic moss, including Cladosporium , Fusarium , and Mortierella 5 . The fungal genera, such as Cladosporium , Mortierella , and Alternaria , were associated with leaves of Arctic plants 6 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Among 78 fungal genera detected in the present study, 11 were previously reported from the Arctic soils, including Acremonium , Alternaria , Arrhenia , Arthrinium , Aspergillus , Cladosporium , Exophiala , Herpotrichia , Mortierella, Phialocephala, Oidiodendron , and Preussia 2 3 4 , and 3 were observed associated with the Arctic moss, including Cladosporium , Fusarium , and Mortierella 5 . The fungal genera, such as Cladosporium , Mortierella , and Alternaria , were associated with leaves of Arctic plants 6 .…”
Section: Discussionsupporting
confidence: 55%
“…Hence, the structure, composition, and taxonomic diversity of microbial communities in the Arctic need to be studied urgently. In particular, fungi are an important proportion of microbial communities in Arctic habitats, such as soil 2 3 4 , mosses 5 , plant leaves 6 7 8 , and plant roots 9 10 11 12 . Lichens are successful colonizers of the Arctic and may play an important role in the mineral cycling patterns of Arctic habitats.…”
mentioning
confidence: 99%
“…In spite of this, both sites are, at present, overgrown by a well-developed moss-lichen tundra with a large number of vascular plants. This is likely due to the high moisture regime and strong ornithogenic fertilization at these sites, both of which are crucial factors in the development of nutrient-rich soil [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…According to Lombard et al (2011) some highly condensed samples (such as soil) are challenging for extraction and their subsequent analyses (even in case of metagenomics analyses). The environmental extremes distinctive for polar regions (such as low temperature, dryness, exposure to UV-radiation, and organic matter deficiency) additionally result in low microbial diversity present in samples (Ali et al 2013). Concluding, some natural enrichment must be present in the studied samples prior the sampling.…”
Section: Introductionmentioning
confidence: 98%